Design And Fabrication Of Multipurpose Smart Phantom For Positron Emission Tomography/Computed Tomography Imaging - Zainon, Rafidah (2008)
Phantom studies are an important part in medical imaging as it can evaluate the performance and quality assurance (QA) test of dual-modality PET/CT. The purpose of this study is to design, fabricate and develop a multipurpose smart phantom which includes the internal structures, water, human tissue, equivalent, material and radioactive source for dual-modality Positron Emission Tomography/Computed Tomography (PET/CT) imaging